2016
DOI: 10.1039/c6ra24651f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and bioevaluation of 2-phenyl-5-methyl-2H-1,2,3-triazole-4-carboxylic acid/carbohydrazide derivatives as potent xanthine oxidase inhibitors

Abstract: A series of 2-phenyl-5-methyl-2H-1,2,3-triazole-4-carboxylic acids/carbohydrazides as analogues of febuxostat were synthesized and evaluated for their in vitro xanthine oxidase (XO) inhibitory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Variation in the position of the three nitrogen atoms within the central five‐membered ring was reported by Shi et al. in their work on 2‐aryl‐5‐methyl‐2 H ‐1,2,3‐triazole‐4‐carboxylic acids 139 and carbohydrazide derivatives 140 . The carbohydrazide derivatives showed no activity at a concentration of 10 μ m , while among the carboxylic acid derivatives, those with a cyano group were generally more active than those with a nitro group.…”
Section: Non‐purine‐like Inhibitors Of Xomentioning
confidence: 99%
“…Variation in the position of the three nitrogen atoms within the central five‐membered ring was reported by Shi et al. in their work on 2‐aryl‐5‐methyl‐2 H ‐1,2,3‐triazole‐4‐carboxylic acids 139 and carbohydrazide derivatives 140 . The carbohydrazide derivatives showed no activity at a concentration of 10 μ m , while among the carboxylic acid derivatives, those with a cyano group were generally more active than those with a nitro group.…”
Section: Non‐purine‐like Inhibitors Of Xomentioning
confidence: 99%
“…23 In comparison with allopurinol, non-purine XOIs like febuxostat and topiroxostat exhibit more outstanding inhibitory activity and lower toxicity, indicating that there is still an urgent need for novel non-purine alternatives with favorable toxicology profile. 1,7,8,16,24,25 As for in silico studies of XOIs, many experiments have been performed to explore the structure-activity relationship (SAR) of febuxostat analogues, topiroxostat analogues and natural compounds, and to design novel compounds. [26][27][28] However, few studies have reported pharmacophore-based virtual screening for XOIs.…”
Section: Introductionmentioning
confidence: 99%
“…2), including pyrazole (3), selenazole (4), imidazole ( 5), isoxazole (6), triazole (8), and pyrimidine (9). 1,7,8,13,16,25 This study focused on the in silico exploration of new XOI scaffolds, which might provide important information for designing novel XOI candidates. The pharmacophore models were constructed to extract the common structural features of febuxostat (1), topiroxostat (2), Y-700 (3), and some aforementioned XOI candidates (4-10).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, trisubstituted N -aryl 1,2,3-triazoles are important scaffolds found in numerous druglike and biologically active molecules, such as c-Met kinase and xanthine oxidase inhibitors, as well as antibacterial, anti-influenza, and other anticancer agents (Scheme a). These functionalized molecules are commonly synthesized from the corresponding substituted alkyl N -aryl 1,2,3-triazole-carboxylates as precursors. Most of these triazole precursors are in turn accessed via multiple steps, especially involving the coupling reactions between aryldiazonium salts and sodium azide. ,− In contrast to the multistep synthesis of such N -aryl 1,2,3-triazole motifs originated from aryldiazonium salts and nitrogen-based synthons, the single-step synthesis based on aryldiazonium salts and other suitable amino-containing reaction partners is exceptionally desirable. Moreover, among these alkyl triazole-carboxylate moieties, drug discovery based on N 2 -aryl triazoles remains hitherto elusive compared with the N 1 -aryl counterparts.…”
mentioning
confidence: 99%
“…N itrogen heterocyclic compounds are ubiquitous structural motifs in the pharmaceutical industry. 1 Particularly, trisubstituted N-aryl 1,2,3-triazoles are important scaffolds found in numerous druglike and biologically active molecules, such as c-Met kinase 2 and xanthine oxidase inhibitors, 3 as well as antibacterial, 4 anti-influenza, 5 and other anticancer agents 6 (Scheme 1a). These functionalized molecules are commonly synthesized from the corresponding substituted alkyl N-aryl 1,2,3-triazole-carboxylates as precursors.…”
mentioning
confidence: 99%